FREKUENSI TINGKAT KESEHATAN PERIODONTAL PADA REMAJA SMP NEGERI 3 BANDA ACEH YANG DIPERIKSA MELALUI CPITN - Nuzulul Ismi; Sunnati .; Zulfan M. Alibasyah (Dentistry Faculty, 2016)
AbstractPeriodontal disease is one of the most common oral health problems. Adolescent is an importantperiod in periodontal status because suffered from periodontal disease is increasing. The number ofadolescent suffered from this disease is increasing and effected in periodontal status. There are severalmethods used in order to measure the severity of periodontal disease, one of the methods is CPITN.The purpose of this study was to identify the frequency of periodontal health on students of SMP 3Baiturrahman Banda Aceh who aged between 12-14. This is a cross sectional descriptive study. Thenumber of subject was 96 students. In detail, there were 33 subjects (34,3%) aged 12, 44 subjects(45,8%) aged 13 and 19 subjects (19,8%) aged 14. Data was collected through interview and clinicalexamination. The result of this study indicated that 26 subjects (27,1%) had a health periodontal tissue(score 0). On the other hand, 1 subject (1%) with bleeding on probing (score 1). Furthermore, 68subjects (70,9%) had both supragingiva/subgingiva calculus (score 2). Only 1 subject (1%) hadabsolute pocket 4-5 mm (score 3). No subject (0%) had absolute pocket 6 mm (score 4). Based onscore CPITN, the kind of proper and effective oral treatment for these subjects are home care, scalling,oral hygiene care and no indicated to complex therapy. It can be concluded that level of periodontalhealth on students of SMP 3 Baiturrahman Banda Aceh who aged between 12-14, 68 subjects (70,9%)had both supragingiva/subgingiva calculus (score 2) and it was the highest score.Keywords: adolescent, CPITN, periodontal status